Asking about life - Tobin, Allan J.; Dusheck, Jennie (Fort Worth : Saunders College Pub., 1998)
This textbook is an introductory biology textbook that presents its chapter and heading sections in the form of questions and begins each chapter with a story about how a biologist or group of biologists asked questions about life in order to investigate biology. Forty-four chapters cover chemistry and cell biology, genetics, evolution, biological diversity, ecology, and structural and physiological adaptations of flowering plants and of animals.
The unity and diversity of life -- pt. 1: Chemistry and cell biology. The chemical foundations of life -- Biological molecules small and large -- Why are all organisms made of cells? -- Directions and rates of biochemical processes -- How do organisms supply themselves with energy? -- Photosynthesis : how do organisms get energy from the sun? -- pt. 2: Genetics : the continuity of life. Cell reproduction -- From meiosis to Mendel -- The structure, replication, and repair of DNA -- How are genes expressed? -- Jumping genes and other unconventional genetic systems -- Genetic engineering and recombinant DNA -- Human genetics -- pt. 3: Evolution. What is the evidence for evolution? -- Microevolution : how does a population evolve? -- Macroevolution : how do species evolve? -- How did the first organisms evolve? -- pt. 4: Diversity. Classification : what's in a name? -- Prokaryotes : how does the other half live? -- Classifying the protists and multicellular fungi -- How did plants adapt to dry land? -- Protostome animals : most animals form mouth first -- Deuterostome animals : echinoderms and chordates -- pt. 5: Ecology. Ecosystems -- Communities : how do species interact? -- Biomes and aquatic communities -- Populations and the human place in the biosphere -- The ecology of animal behavior -- pt. 6: Structural and physiological adaptations of flowering plants. Structural and chemical adaptations of plants -- What drives water up and sugars down? -- Growth and development of flowering plants -- How do plant hormones regulate growth and development? -- pt. 7: Structural and physiological adaptations of animals. Form and function in animals -- How do animals obtain nourishment from food? -- How do animals coordinate cells and organs? -- Blood, circulation, and the heart -- How do animals obtain and distribute oxygen? -- How do animals manage water, salts, and wastes? -- Defense : inflammation and immunity -- The cells of the nervous system -- The nervous system and the sense organs -- Sexual reproduction -- How do organisms become complex?
Includes bibliographical references and index.
Keywords: Biology